Perancangan Komik Edukasi Cosplay untuk Generasi Muda di Indonesia - Glennesha Geneviene; Irwan Harnoko (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
Cosplay (コスプレ, kosupure) is an act in which someone imitates the identity or character of an anime, comic, cartoon, or another famous character by wearing clothes, hats, wigs, shoes, and other accessories. The development of cosplay as pop culture in Indonesia provides many opportunities for ordinary people, especially teenagers, to start this hobby. However, there are still many beginner teenagers and ordinary people who do not have the resources to start cosplay. Therefore, designing comics as an educational medium to start cosplay is very much needed so that beginners can get direction and get the essence of cosplay in it. The method used in this design is qualitative descriptive and phenomenology with professional cosplayers, the Surabaya cosplay community (COSURA), and also comic artist Kang Cilok. The results of this study are expected to provide education on how to start a cosplay hobby for beginners in an entertaining way and can be used as a reference for the development of further educational comics.